Sustained alterations in biodistribution of stem/progenitor cells in Tie2Cre+α4(f/f) mice are hematopoietic cell autonomous - Priestley, Gregory V. (American Society of Hematology, 2007)
We have generated Tie2Cre+α4(f/f) mice with documented α4-integrin ablation in hematopoietic and endothelial cells. A prominent feature in this model is a sustained, significant increase in circulating progenitors at levels higher than the levels seen with Tie2Cre+VCAM-1(f/f) mice. To test whether phenotypic differences are due to contributions by ligands other than VCAM-1 in bone marrow, or to α4-deficient endothelial cells or pericytes, we carried out transplantation experiments using these mice as donors or as recipients. Changes in progenitor biodistribution after transplantation were seen only with α4-deficient donor cells, suggesting that these cells were necessary and sufficient to reproduce the phenotype with no discernible contribution by α4-deficient nonhematopoietic cells. Because several similarities are seen after transplantation between our results and those with CXCR4(−/−) donor cells, the data suggest that VLA4/VCAM-1 and CXCR4/CXCL12 pathways contribute to a nonredundant, ongoing signaling required for bone marrow retention of progenitor cells during homeostasis.